2011
DOI: 10.1007/s10096-011-1471-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterisation of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli isolates in healthy volunteers in Tunisia

Abstract: The objective of this investigation was to analyse the carriage rate of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli in faecal samples of healthy humans in Tunisia and to characterise the recovered isolates. One hundred and fifty samples were inoculated on MacConkey agar plates supplemented with cefotaxime (2 μg/ml) for ESBL-positive E. coli recovery. The characterisation of ESBL genes and their genetic environments, detection of associated resistance genes, multilocus sequence typing (ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
55
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 27 publications
10
55
4
Order By: Relevance
“…In our study, the prevalence of ESBL-E. coli carriage in stool was as high as 66.3%. This is much higher than in a 2012 study in northern Cameroon which reported a prevalence of 23.1% among community outpatients [3] or in other African studies which reported rates of 30.9 % in Niger [10], 10% in Senegal [11] and 7.3 % in Tunisia [12]. This is even higher to what has been reported in China where a rate of 50.5% of CTX-M-E. coli [13] was described.…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, the prevalence of ESBL-E. coli carriage in stool was as high as 66.3%. This is much higher than in a 2012 study in northern Cameroon which reported a prevalence of 23.1% among community outpatients [3] or in other African studies which reported rates of 30.9 % in Niger [10], 10% in Senegal [11] and 7.3 % in Tunisia [12]. This is even higher to what has been reported in China where a rate of 50.5% of CTX-M-E. coli [13] was described.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been less frequent among susceptible isolates (13,30,41), but the apparent ease with which it acquired resistance combined with its virulence has fuelled its pandemic spread (13). Except for a few studies (27,40), ST131 has been the dominant clone in most studies on ESBL-producing E. coli (6,13,31,35,42); therefore, its high frequency here was not surprising. The lowest rate in GI is concordant with other reports from Spain and Barcelona (33,43,44); so are the higher rates in France (BM) and Italy (FS) (41,45).…”
Section: Resultsmentioning
confidence: 99%
“…It is easier to understand why just single isolates of ST73 (in FS) and ST95 (TA) were identified. These highly pathogenic clones have frequently been recovered from clinical samples but rarely, if at all, with ESBLs (29,34,(49)(50)(51), which may explain their absence in the analyses targeted on ESBL-positive E. coli isolates (27,31,32,44). MLST versus PFGE.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, nearly half of them belonged to CCs ST10 and ST58. ST10 and ST58 have both a global distribution, and they have been isolated from humans as well as animals (41)(42)(43)(44). The K. pneumoniae outbreak in Uppsala was also caused by a global clone, ST16 (12), which in recent years has been associated with several clinically important carbapenemases (45).…”
Section: Discussionmentioning
confidence: 99%